Therapeutic monoclonal antibody for sporotrichosis - Almeida, Sandro (Frontiers in Microbiology, 2012)
Sporotrichosis is a chronic subcutaneous mycosis that affects both humans and animals worldwide. This subcutaneous mycosis had been attributed to a single etiological agent, Sporothrix schenckii. S. schenckii exhibits considerable genetic variability, and recently, it was suggested that this taxon consists of a complex of species. Sporotrichosis is caused by traumatic inoculation of the fungus, which is a ubiquitous environmental saprophyte that can be isolated from soil and plant debris. The infection is limited to cutaneous forms, but recently, more severe clinical forms of this mycosis have been described, especially among immunocompromised individuals. The immunological mechanisms involved in the prevention and control of sporotrichosis are not well understood. Some studies suggest that cell-mediated immunity plays an important role in protecting the host against S. schenckii. In contrast, the role of the humoral immune response in protection against this fungus has not been studied in detail. In a previous study, we showed that antigens secreted by S. schenckii induced a specific humoral response in infected animals, primarily against a 70-kDa molecule, indicating a possible role of specific antibodies against this molecule in infection control. In another study by our group, we produced a mAb against a 70-kDa glycoprotein of S. schenckii to better understand the effect of the passive immunization of mice infected with S. schenckii. The results showed a significant reduction in the number of CFUs in various mice organs when the mAb was injected before or during S. schenckii infection. Similar results were observed when T-cell-deficient mice were used. The drugs of choice in the treatment of sporotrichosis require long periods, and relapses are frequently observed, primarily in immunocompromised patients. The strong protection induced by the mAb against a 70-kDa glycoprotein makes it a strong candidate as a therapeutic vaccine against sporotrichosis.